Beyond single drivers: A multi-stressor framework for understanding and managing jellyfish proliferation under concurrent anthropogenic and climate pressures - Clémence Epinoux; Delphine Bonnet; Sandra Bringay; Matthieu de Castelbajac; Eduardo Ramirez-Romero; Arnaud Sallaberry; Marco Scotti; Maximilien Servajean; Juan-Carlos Molinero (Ocean & Coastal Management, 2025)

Synthesis of polysaccharide-based block copolymers obtained by click chemistry from opened β-cyclodextrin and growth polymerization - Dindet Steve Evanes Koffi Teki; Hajeeth Thankappan; Matthieu Pélingre; Mariama Ndour; Cédric Przybylski; Emmanuel Petit; Julien Bernard; Véronique Bonnet; Eric Drockenmuller; José Kovensky (Carbohydrate Polymers, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Iron-binding by dissolved organic matter in the Western Tropical South Pacific Ocean (GEOTRACES TONGA cruise GPpr14) - Léo Mahieu; Hannah Whitby; Gabriel Dulaquais; Chloé Tilliette; Catherine Guigue; Marc Tedetti; Dominique Lefevre; Pierre Fourrier; Matthieu Bressac; Géraldine Sarthou; Sophie Bonnet; Cécile Guieu; et al. (Frontiers in Marine Science, 2024)
Iron (Fe) is an essential micronutrient for phytoplankton growth, but its scarcity in seawater limits primary productivity across much of the ocean. Most dissolved Fe (DFe) in seawater is complexed with Fe-binding organic ligands, a poorly constrained fraction of dissolved organic matter (DOM), which increase Fe residence time and impact Fe bioavailability. Here, we present the conditional concentration (L Fe ) and binding-strength (log K F e ' L c o n d ) of Fe-binding ligands in the Western Tropical South Pacific (WTSP) Ocean during the GEOTRACES TONGA cruise (GPpr14). The transect crossed the Lau basin, a region subject to shallow hydrothermal Fe inputs that fuel intense diazotrophic activity, the oligotrophic South Pacific gyre, and the Melanesian basin. Organic speciation was analyzed by competitive ligand exchange adsorptive cathodic stripping voltammetry (CLE-AdCSV) using salicylaldoxime at 25 µM. We found a high mean L Fe of 5.2 ± 1.2 nMeqFe (n = 103) across the entire transect, predominantly consisting of intermediate strength L2 ligands (84%; mean log K F e ' L c o n d of 11.6 ± 0.4), consistent with humic-like substances. DFe correlated with the humic-like component of the fluorescent DOM (HS-like FDOM), yet the electroactive Fe-binding humic-like substances (L FeHS ) accounted for only 20 ± 13% of L Fe in the mixed layer and 8 ± 6% in deep waters. Ligands were in large excess compared to DFe (mean excess ligand eL Fe = 4.6 ± 1.1 nMeqFe), suggesting poor stabilization of DFe inputs. High L Fe (up to 9 nMeqFe) in samples close to hydrothermal sites could be due to detoxification strategies from plankton communities toward hydrothermally-fueled toxic trace metals other than Fe, with an apparent dilution of the DOM from the Lau basin into neighboring regions. We also observed a different peak potential of the Fe salicylaldoxime complex detected by CLE-AdCSV between the Lau and Melanesian basins, and between surface and deep waters. To our knowledge, this change in potential has not previously been reported; whether this represents a novel detection of specificities in DOM composition merits further investigation. Competition between Fe and competing metals for ligand binding sites could favor DFe oxidation and precipitation near hydrothermal vents and explain the absence of strong Fe stabilization in the WTSP.

Seabird Migration Strategies: Flight Budgets, Diel Activity Patterns, and Lunar Influence - Anne-Sophie Bonnet-Lebrun; Maria P. Dias; Richard A. Phillips; José P. Granadeiro; M. de L. Brooke; Olivier Chastel; Thomas A. Clay; Annette L. Fayet; Olivier Gilg; Jacob González-Solís; Tim Guilford; Sveinn A. Hanssen; et al. (Frontiers in Marine Science, 2021)
Every year, billions of birds undertake extensive migrations between breeding and non-breeding areas, facing challenges that require behavioural adjustments, particularly to flight timing and duration. Such adjustments in daily activity patterns and the influence of extrinsic factors (e.g., environmental conditions, moonlight) have received much more research attention in terrestrial than marine migrants. Taking advantage of the widespread deployment in recent decades of combined light-level geolocator-immersion loggers, we investigated diel organisation and influence of the moon on flight activities during the non-breeding season of 21 migrant seabird species from a wide taxonomic range (6 families, 3 orders). Migrant seabirds regularly stopped (to either feed or rest) during migration, unlike some terrestrial and wetland birds which fly non-stop. We found an overall increase for most seabird species in time in flight and, for several species, also in flight bout duration, during migration compared to when resident at the non-breeding grounds. Additionally, several nocturnal species spent more of the day in flight during migration than at non-breeding areas, and vice versa for diurnal species. Nocturnal time in flight tended to increase during full moon, both during migration and at the non-breeding grounds, depending on species. Our study provides an extensive overview of activity patterns of migrant seabirds, paving the way for further research on the underlying mechanisms and drivers.

No longer locally extinct? Tracing the origins of a lion (Panthera leo) living in Gabon - Ross Barnett; Mikkel-Holder S. Sinding; Filipe G. Vieira; Marie Lisandra Zepeda Mendoza; Matthieu Bonnet; Alessandro Araldi; Ivonne Kienast; Alice Zambarda; Nobuyuki Yamaguchi; Philipp Henschel; M. Thomas P. Gilbert (Conservation Genetics, 2018)

Nest design in a changing world: Great tit Parus major nests from a Mediterranean city environment as a case study - Marcel M. Lambrechts; Anne Charmantier; Virginie Demeyrier; Annick Lucas; Samuel Perret; Matthieu Abouladzé; Michel Bonnet; Coline Canonne; Virginie Faucon; Stéphanie Grosset; Gaëlle le Prado; Frédéric Lidon; et al. (Urban Ecosystems, 2017)

Selenoprotein T Deficiency Leads to Neurodevelopmental Abnormalities and Hyperactive Behavior in Mice - Matthieu T. Castex; Arnaud Arabo; Magalie Bénard; Vincent Roy; Vadim Le Joncour; Gaëtan Prévost; Jean-Jacques Bonnet; Youssef Anouar; Anthony Falluel-Morel (Molecular Neurobiology, 2016)

Nest-box size influences where secondary-cavity exploiters roost and nest: a choice experiment - Marcel M. Lambrechts; Matthieu Abouladzé; Michel Bonnet; Virginie Demeyrier; Claire Doutrelant; Virginie Faucon; Gaëlle le Prado; Frédéric Lidon; Thierry Noell; Pascal Pagano; Philippe Perret; Stéphane Pouplard; et al. (Journal of Ornithology, 2013)